Fibrosis‐4 index reflects right ventricular function and prognosis in heart failure with preserved ejection fraction. (24th March 2021) - Nakashima, Mitsutaka; Sakuragi, Satoru; Miyoshi, Toru; Takayama, Shin; Kawaguchi, Tatsuto; Kodera, Nobuhisa; Akai, Hiroaki; Koide, Yuji; Otsuka, Hiroaki; Wada, Tadashi; Kawamoto, Kenji; Tanakaya, Machiko; et al.
Abstract: Aims: Fibrosis‐4 index (FIB‐4 index), calculated by age, aspartate aminotransferase, alanine aminotransferase, and platelet count, is a simple marker to evaluate liver fibrosis and is associated with right‐sided heart failure. However, the clinical relevance of FIB‐4 in patients with heart failure with preserved ejection fraction (HFpEF) remains unclear. We investigated the prognostic implication of the FIB‐4 index regarding right ventricular dysfunction in patients with HFpEF. Methods and results: This prospective study included 116 consecutive HFpEF patients (mean age 79 years, 43% male) hospitalized with acute decompensated heart failure. We evaluated the association of the FIB‐4 index with right ventricular function determined by tricuspid annular plane systolic excursion (TAPSE) and tricuspid lateral annular systolic velocity (S′) before discharge. Cox regression analysis was performed to evaluate the association between the FIB‐4 index and major adverse cardiovascular events (MACE) defined as the composite of cardiovascular death, readmission for heart failure, nonfatal myocardial infarction, and nonfatal stroke. FIB‐4 index before discharge was significantly lower than that at admission (2.62 [1.92–3.46] and 3.03 [2.05–4.67], median [interquartile range], P < 0.001). Left ventricular ejection fraction, TAPSE, and S′ before discharge were 62.7 (55.9–68.6) %, 17.5 ± 4.6 mm (mean ± standard deviation), and 10.0 (8.0–12.0) cm/s, respectively. In multiple linear regression analysis, the FIB‐4 index before discharge was inversely correlated with TAPSE (β minus;0.244, P = 0.014) and S′ (β −0.266, P = 0.009). During a median follow‐up of 736 days, 37 MACE occurred. Multivariate Cox regression analysis revealed that a high FIB‐4 index before discharge (per 1 point) was a significant predictor of MACE (hazard ratio 1.270, 95% confidence interval 1.052–1.532) after adjustment for male, serum creatinine, and haemoglobin. Receiver operating characteristic analysis indicated that the optimal cut‐off value of FIB‐4 index before discharge to predict MACE was 3.11. Kaplan–Meier survival analysis showed that patients with a FIB‐4 index before discharge ≥3.11 had a significantly poorer prognosis than patients with FIB‐4 index before discharge <3.11 ( P = 0.029). Patients with an FIB‐4 index ≥3.11 had a 2.202‐fold (95% confidence interval 1.110–4.368) increased risk of MACE compared with those with an FIB‐4 index <3.11 after adjustment for male, serum creatinine, and haemoglobin. Conclusions: An increase in the FIB‐4 index was associated with right ventricular dysfunction and a higher risk of future MACE in patients with HFpEF.